Efecto del hidrogel en el crecimiento y supervivencia de diferentes materiales de plátano en secano - Intriago Alcívar, Carlos Nijel (2024)
The objective of the research was to evaluate the effect of the hydrogel on the growth and survival of different dry plantain materials. Factorial treatments of four levels of hydrogel (25, 50, 75 and 100 g plant-1) and two planting materials (corms and nursery seedlings) were evaluated, with two control treatments with corms and seedlings with irrigation. Soil water tension, photochemical activity of photosystem II (PSII) as effective quantum yield (ΦPSII), maximum quantum efficiency (Fv/Fm), electron transport rate (ETR), relative water content in the leaf (RWC), specific leaf area (SLA), chlorophyll content (SPAD units) and dry matter accumulation over time. With the use of hydrogel, soil moisture was maintained in field capacity ranges for up to 60 days for corm plants and up to 30 days for nursery plants. Physiological activity (ΦPSII, Fv/Fm, ETR, RWC, SLA, SPAD chlorophyll) was maintained at adequate levels to guarantee good photosynthetic activity, survival and active growth of dryland plants, so as not to cause photoinhibition or physiological damage. With irrigation the physiological activity and growth of the plants was greater. The growth and survival of the banana was enhanced by the hydrogel, and therefore planting early in the rainy season in dryland systems can be recommended.